Influence of closed skill and open skill warm-ups on the performance of speed, change of direction speed, vertical jump, and reactive agility in team sports athletes - Gabbett, T. J.; Sheppard, J. M.; Pritchard-Peschek, K. R.; Leveritt, M. D.; Aldred, M. J. (The Journal of Strength and Conditioning Research, 2008)
In this study, we evaluated the efficacy of two different dynamic warm-up conditions, one that was inclusive of open skills (i.e., reactive movements) and one that included only preplanned dynamic activities (i.e., closed skills) on the performance of speed, change of direction speed, vertical jump, and reactive agility in team sport athletes. Fourteen (six male, eight female) junior (mean +/- SD age, 16.3 +/- 0.7 year) basketball players participated in this study. Testing was conducted on 2 separate days using a within-subjects cross-over study design. Each athlete performed a standardized 7-minute warm-up consisting of general dynamic movements and stretching. After the general warm-up, athletes were randomly allocated into one of two groups that performed a dynamic 15-minute warm-up consisting entirely of open or closed skills. Each of the warm-up conditions consisted of five activities of 3 minute duration. At the completion of the warm-up protocol, players completed assessments of reactive agility, speed (5-, 10-, and 20-m sprints), change of direction speed (T-test), and vertical jump. No significant differences (p > 0.05) were detected among warm-up conditions for speed, vertical jump, change of direction speed, and reactive agility performances. The results of this study demonstrate that either open skill or closed skill warm-ups can be used effectively for team sport athletes without compromising performance on open skill and closed skill tasks.